Impact of ChatGPT usage on nursing students education: A cross-sectional study - Alberto Gonzalez-Garcia; David Bermejo-Martinez; Ana Isabel Lopez-Alonso; Bibiana Trevisson-Redondo; Cristian Martín-Vázquez; Silvia Perez-Gonzalez (Heliyon, 2025)
Background: The use of artificial intelligence tools, such as ChatGPT, is on the rise in nursing education. In the field of healthcare, ChatGPT can offer unique opportunities to enhance the learning and clinical practice of nursing students. However, it is still necessary to explore how this tool affects students' performance and perception in their nursing education. Objective: The objective of this study was to evaluate the impact of ChatGPT on nursing students' education and determine how it influences their learning outcomes. Design: This study employed a quantitative cross-sectional design. Setting: The study was conducted in the Bachelor of Nursing program at the University of León, Spain. Participants: Ninety-eight nursing students enrolled in the Nursing Care and Services Management course during the second semester of 2024 participated in the study. Methods: Data were collected using three validated questionnaires that assessed sociodemographic characteristics, knowledge of artificial intelligence, and perceptions of using ChatGPT as an educational tool. The data were analyzed using IBM SPSS Statistics, version 29.1. Results: Students who used ChatGPT showed a significant improvement in their academic grades (p < 0.05). Additionally, 89.5 % of the students reported significant improvements in their academic performance. Women perceived ChatGPT as especially useful for completing academic tasks (85.14 % versus 50.00 % in men, p = 0.003). A positive correlation was observed between prior use of ChatGPT and GPA (ρ = 0.240, p = 0.026). Conclusions: ChatGPT is a valuable tool that enhances the learning and satisfaction of nursing students. Its integration into nursing education programs not only boosts academic performance but also promotes the adoption of technological innovations in professional training. Continuous incorporation of AI tools in education is recommended to improve academic outcomes and prepare students for evolving healthcare environments.